Microenvironments’ Fine-Scale Influence on Amphibian Communities in Chengdu Plain - Xiaoqin Shi; Zhiyu Dong; Xiaoke Liu; Ziyan Liao; Yongbin Wu; Youhua Chen (Ecosystem Health and Sustainability)
In community ecology, a species-poor site’s species should be part of a richer site’s species. This ecological pattern, known as nestedness, is intrinsically related to β diversity, yet their relationship remains insufficiently explored, particularly at the single-species and single-site levels. Various ecological processes explain nestedness, but a comprehensive assessment of its ties to β diversity is lacking. Here, we evaluated the multi-scale effects of environmental factors on the community structure, measured as single site-level or single species-level nestedness and β diversity metrics, with amphibian communities in rural habitats of Chengdu City, southwestern China. Our multi-scale analyses were conducted through varying sampling range sizes (determining the values of environmental factors within each line transect) within different study extents (determining the joining of different line transects, the aggregation of environmental factors, and the combination of amphibian composition). Furthermore, we examined the interrelationship between individual-level nestedness and β diversity across these spatial scales. Our results demonstrated that single site-level nestedness and single site-level β diversity did not exhibit a consistent positive linear correlation, with their relationship contingent on spatial scale. Environmental factors were found to influence both nestedness and β diversity components, although these effects were statistically marked only at smaller spatial extents (line-transect or sampling-site level), highlighting the crucial role of the microhabitat heterogeneity in structuring amphibian communities. Collectively, this study provides novel insights into the general relationships between environmental variables and community structure patterns (β diversity and nestedness) through the lens of single-species and single-site perspectives.